Empyema of the Ureteral Stump. An Unusual Complication Following Nephrectomy - Apostolos P. Labanaris; Vahudin Zugor; Robert Smiszek; Reinhold Nützel; Reinhard Kühn (The Scientific World Journal)
A ureteral stump, which is the segment of the ureter left in place after nephrectomy, may occasionally give rise to a pathologic process called ureteral stump syndrome, which is clinically interpreted as febrile urinary tract infections, lower quadrant pain, and hematuria. Empyema of the ureteral stump, which belongs to this syndrome, is an uncommon disease entity presenting with a reported incidence of 0.8–1%. We present a case of empyema of the ureteral stump in a female patient 5 years postnephrectomy for a nonfunctioning kidney, and discuss the clinical presentation, radiologic diagnosis, and therapeutic options of this uncommon disease entity.